The Effect of Cooling Water Inlet Emperature (CWIT) on Efficiency USC 1050 MW Steam Power Plant - Hiro Nayaparana; Purwanto Purwanto; Endang Kusdiyantini (Journal La Multiapp, 2026)
This research explores the impact of the Cooling Water Inlet Temperature (CWIT) on the efficiency and operational costs of the Ultra Supercritical (USC) 1050 MW Coal-Fired Power Plant (PLTU) in Indonesia. With Indonesia's growing dependence on PLTU as a primary source of electricity, maintaining operational efficiency is critical. The study was conducted at the PLTU Jawa 7 change to 1050 USC type power plan using quantitative descriptive-analytical methods, and data was collected from both the Distributed Control System (DCS) and BMKG. The analysis focuses on how varying CWIT affects condenser pressure, thermal efficiency, Net Plant Heat Rate (NPHR), and fuel consumption. The findings indicate that an increase in CWIT results in higher condenser pressure, reduced vacuum quality, and lower thermal efficiency, leading to an increase in NPHR and higher fuel costs. Furthermore, the research assesses the economic impact, highlighting daily fuel cost penalties and opportunity losses due to reduced electricity generation. The study also provides strategies for mitigating the negative effects of CWIT, including enhanced cooling water flow, condenser cleaning, and the addition of cooling towers. In conclusion, the research emphasizes the importance of controlling CWIT to optimize plant performance and reduce operational costs.